2014
DOI: 10.2478/intox-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood and bone marrow responses under stress of cypermethrin in albino rats

Abstract: Pyrethroids, commercially available pesticides, are greatly in use these days, and thus they carry considerable chances of contaminating various ecosystems. Haematotoxicity of cypermethrin, a broadly used type II pyrethroid, has been assessed in the present study. Selected parameters included determination of total RBC count, haemoglobin concentration (Hb conc.), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…These findings supported the results of Pande et al (2014) and Dar & Kaur (2014) who detected a significant decrease in the total RBCs count, hemoglobin concentration, PCV, MCV, and MCH, while TLC and DLCs were significantly increased on cutaneous exposure of cypermethrin, a type II synthetic pyrethroid insecticide. Thereafter, Narra (2016) reported that pyrethroid exposure causes dwindling of blood respiratory burst activity, RBCs count, hematocrit value and hemoglobin concentration with elevated white blood cell count, lipid peroxidation levels and reduction of glutathione levels and glutathione peroxidase activity Also, Aroonvilairat et al, (2018) observed significant changes in various biological parameters including hematotoxicity that was manifested as increased leukocyte counts and percent neutrophil, with decreased RBC count.…”
Section: Discussionsupporting
confidence: 90%
“…These findings supported the results of Pande et al (2014) and Dar & Kaur (2014) who detected a significant decrease in the total RBCs count, hemoglobin concentration, PCV, MCV, and MCH, while TLC and DLCs were significantly increased on cutaneous exposure of cypermethrin, a type II synthetic pyrethroid insecticide. Thereafter, Narra (2016) reported that pyrethroid exposure causes dwindling of blood respiratory burst activity, RBCs count, hematocrit value and hemoglobin concentration with elevated white blood cell count, lipid peroxidation levels and reduction of glutathione levels and glutathione peroxidase activity Also, Aroonvilairat et al, (2018) observed significant changes in various biological parameters including hematotoxicity that was manifested as increased leukocyte counts and percent neutrophil, with decreased RBC count.…”
Section: Discussionsupporting
confidence: 90%
“…Pyrethroids are considered comparatively safe pesticides and therefore many new synthetic analogues have been added to the market. Contrary to their broad spectrum of use due to their low photostability and non-target toxicity, they can disturb various ecological balances existing on this planet (Rana et al ., 2008; Bhushan et al ., 2013; Pande et al ., 2014, Saxena & Gaur, 2016; Saxena & Bhushan, 2017). We have therefore evaluated and compared hepatocytic toxicity of two broadly used types pyrethroid pesticides, i.e.…”
Section: Introductionmentioning
confidence: 99%